2010
DOI: 10.1103/physrevb.82.075404
|View full text |Cite
|
Sign up to set email alerts
|

Role of electronic friction during the scattering of vibrationally excited nitric oxide molecules from Au(111)

Abstract: Some time ago, it has been observed that vibrationally highly excited NO͑v͒ molecules ͑with typical vibrational quantum numbers v Ϸ 15͒ lose substantial amounts of vibrational energy when scattering off a Au͑111͒ surface ͓H. Huang, C. Rettner, D. Auerbach, and A. Wodtke, Science 290, 111 ͑2000͔͒. This has been interpreted as a sign for the breakdown of the Born-Oppenheimer approximation due to vibration-electron coupling. It has been argued that this process cannot be understood on the basis of single-quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
88
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 50 publications
(42 reference statements)
3
88
1
1
Order By: Relevance
“…For example, multi-quantum vibrational relaxation of NO(v = 14,15) on Au(111) is at least semi-quantitatively reproduced by friction-like theories. 13 However, good agreement with experiment is also found using a multi-state (independent electron surface hopping) model, [14][15][16] where a single electron transfer mechanism is operative.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…For example, multi-quantum vibrational relaxation of NO(v = 14,15) on Au(111) is at least semi-quantitatively reproduced by friction-like theories. 13 However, good agreement with experiment is also found using a multi-state (independent electron surface hopping) model, [14][15][16] where a single electron transfer mechanism is operative.…”
mentioning
confidence: 75%
“…For example, multi-quantum vibrational relaxation of NO(v = 14,15) on Au(111) is at least semi-quantitatively reproduced by friction-like theories. 13 However, good agreement with experiment is also found using a multi-state (independent electron surface hopping) model, 14-16 where a single electron transfer mechanism is operative.Putting it another way, a fundamental unknown is the fraction of molecular vibration that can be converted to single electron excitation and vice versa. For example, one might envision that a single highly excited electron in a solid could transfer nearly all of its excitation energy to a molecule at the surface.…”
mentioning
confidence: 81%
“…Thus, Shenvi et al 12,13 have been able to explain the observed multi-quantum vibrational relaxation of NO scattered from Au(111) using a model that incorporates electron hopping between the surface and the molecule. More recently, low dimensional calculations performed by Monturet et al 14 suggest that an electronic friction model may also account for many of the results obtained in this kind of experiment.…”
Section: Introductionmentioning
confidence: 98%
“…Experimental results showed that NO in high vibrational states (v i = 15), incident with translational energy of 0.05 eV, relax into a broad range of vibrational states when scattered from a gold surface. 16 Several different theoretical approaches semi-quantitatively reproduce the observed vibrational state distributions, including a Monte Carlo model with stochastic quantum jumps between the neutral and negative ion states of the molecule, 17 fully quantum mechanical first-principles EF theory, 18 and molecular dynamics (MD) employing Independent Electron Surface Hopping (IESH) on a density functional theory (DFT) based Newns-Anderson Hamiltonian. [19][20][21][22] In order to attempt to distinguish between these various theoretical approaches, a comprehensive series of experiments was performed to study the collision-induced vibrational excitation of NO(v = 0) into vibrational states v = 1, 2 when scattered from a Au(111) surface over a wide range of incidence energies and surface temperatures (300 K ≤ T s ≤ 1000 K and 0.11 eV ≤ E i ≤ 1.05 eV).…”
Section: Introductionmentioning
confidence: 99%